Pendekatan Kontekstual dalam Meningkatkan Pembelajaran Pendidikan Pancasila dan Kewarganegaraan di Sekolah Dasar - Parhan, Muhamad; Sukaenah, Sukaenah (Universitas Negeri Malang, 2020)
This study aimed to offer an alternative reconstruction of the fifth-grade Pancasila and Civic Education learning process at SDN Cugenang. This was done on the basis of thefinding that the learning that has been held so far tends to be theoretical-abstract and difficult for students to understand. The method used was a classroom action research method with four stages of activity, namely: planning, action, observation, and reflection, which are carried out in three cycles. In general, it could be concluded that Pancasila and Civic Education learning held in elementary schools with a contextual approach could make the learning process and outcomes better and more improved.